1989
DOI: 10.1111/j.1464-410x.1989.tb05281.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Stamey and Pereyra‐Raz Bladder Neck Suspensions

Abstract: Endoscopic bladder neck suspension has become one of the more popular methods of surgical treatment of stress incontinence. The Pereyra technique was first described in 1959 and modified by Raz in 1981. Stamey first described his technique in 1973 and this has been modified in a number of ways. The reported cure rates are 54 to 94% for the Pereyra-Raz procedure and 61 to 92% for the Stamey procedure. We present a comparative review of the technical results of treatment of 30 patients with a modified Stamey pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 11 publications
0
10
0
2
Order By: Relevance
“…In unserer Studie fanden wir keine einzelne präoperative Variable, die signifikant mit dem Auftreten einer Rezidivinkontinenz verknüpft war. In einer Vielzahl von Untersuchungen hat sich die Blasenhalssuspension nach Stamey als äquivalent im Vergleich zu anderen Inkontinenzoperationen gezeigt, insbesondere im Vergleich zur Vesikourethropexie nach Marshall-Marchetti-Krantz [7,23,28], zu Kolposuspensionsoperationen [20], zu Schlingeneingriffen [11], zur vorderen Plastik [16] und zur Raz-Blasenhalssuspension [21]. Im Gegensatz zu allen präoperativen Parametern hatten Komplikationen im postoperativen Verlauf einen signifikanten Einfluß auf das ope- Die erhebliche Variationsbreite in der berichteten Häufigkeit von postoperativen Komplikationen beruht in erster Linie auf der unterschiedlichen Definition einer postoperativen Komplikation.…”
Section: Diskussionunclassified
“…In unserer Studie fanden wir keine einzelne präoperative Variable, die signifikant mit dem Auftreten einer Rezidivinkontinenz verknüpft war. In einer Vielzahl von Untersuchungen hat sich die Blasenhalssuspension nach Stamey als äquivalent im Vergleich zu anderen Inkontinenzoperationen gezeigt, insbesondere im Vergleich zur Vesikourethropexie nach Marshall-Marchetti-Krantz [7,23,28], zu Kolposuspensionsoperationen [20], zu Schlingeneingriffen [11], zur vorderen Plastik [16] und zur Raz-Blasenhalssuspension [21]. Im Gegensatz zu allen präoperativen Parametern hatten Komplikationen im postoperativen Verlauf einen signifikanten Einfluß auf das ope- Die erhebliche Variationsbreite in der berichteten Häufigkeit von postoperativen Komplikationen beruht in erster Linie auf der unterschiedlichen Definition einer postoperativen Komplikation.…”
Section: Diskussionunclassified
“…Although in theory the modified Pereyra procedure, with its low morbidity and rapid recovery without complications or significant voiding difficulties, is an ideal operation for the elderly and frail female with genuine stress incontinence, its use must be questioned in view of the poor success rate here. Other authors [9,11] report results better than these but they are subjective, as postoperative urodynamic studies were not routinely carried out. They also report improvement rates and include these as successful operations.…”
Section: Discussionmentioning
confidence: 90%
“…Peattie and Stanton [10] specifically report cure rates in the elderly, with a subjective cure rate of 56% and an objective cure rate of 43% at 2 years. Shah and Holder [11] reported on patients between the ages of 32 and 67, and Raz et al [9] reported on women aged 15-87 (mean 59 years). Hilton and Mayne [15] analyzed the results of the elderly separately, and found an increased cure rate of 76% in those over 65 years compared with younger women (53%) using a modified Stamey procedure.…”
Section: Discussionmentioning
confidence: 97%
“…Technical consideration existed regarding the need to free the retropubic space to transfer the sutures from the vagina to the suprapubic region using fingertip guidance, therefore decreasing the risk of bladder injury but increasing the risk of retropubic bleeding. These procedures enjoyed good results for stress incontinence with promising results in the short term, however provided no support of the upper anterior vagina [22][23][24].…”
Section: Chronology Of Proceduresmentioning
confidence: 95%